Designing school together, between pedagogy and architecture - Weyland, Beate (2018)
This article presents some findings from a research project carried out together with architect Sandy Attia between 2010-2014 funded by the Department of Education of the Free University of Bolzano (Weyland, Attia, 2015). The research frames 10 case studies of schools built in the past decade (preschools, kindergartens and primary schools) in the context of the contemporary debate surrounding the relationship between architecture and pedagogy in the South Tyrol region of Italy. The focus of theresearch resides in the processes that lead up to the design and construction of a new or renovated school, analyzing the trajectories that each project takes in relationship to the projects’ final outcomes. The research posits a need for a shared language between the pedagogical and architectural fields to better navigate the arduous path towards the building of a new school, and underscores the benefits of involving the various stakeholders in the planning of the school to help the institution work to its fullest potential upon resuming the scholastic activities in the newly designed spaces. One of the important findings of the research is the school body’s apparent difficulty in cohesively communicating their teaching and learning needs and the subsequent missteps that can occur from an administrative and architectural standpoint in addressing the programming of the school. In many cases, the school representatives and the architects commissioned to design the new school found themselves working with little common ground and at different paces that were often difficult to reconcile under tight budgets and timeframes. The research also traces important notable changes in the head teacher’s newly invested role in being able to surmount strict school-building codes (within reason) as need be to better accommodate innovative teaching and learning methods. As a result, the face of the school, from a pedagogical and architectural standpoint, is changing in palpable and exciting ways.